ANALYSIS OF THE EFFECT OF FOOD QUALITY AND BRAND IMAGE ON PURCHASE DECISIONS IN ILOCAKE KOTA BIMA - Nurasyiah Nurasyiah; Ismunandar Ismunandar (Jurnal Ilmu Manajemen Profitability, 2022)
This study aims to identify and analyze the effect of food quality and brand image on purchasing decisions at Ilocake Kota Bima. This type of research is associative, the research instrument used is a Likert scale questionnaire. The population in this study are all consumers who have bought products in Ilocake, Bima City whose number is not known with certainty (Unknown Population). The sample in this study were 100 respondents who had bought products in Ilocake Kota Bima using the unknown population formula. The sampling technique used is purposive sampling technique. The data analysis technique used is validity test, reliability test, classical assumption test, multiple linear regression analysis, multiple correlation, determination test, t test and f test. The results of the t-test statistical research indicate that there is an influence between food quality and brand image that affects purchasing decisions in Ilocake, Bima City. The results of the f statistical test state that the Food Quality and Brand Image jointly influence the Purchasing Decision at Ilocake, Bima City